Awareness to Deepfake: A resistance mechanism to Deepfake - Ahmed, Mohammad Faisal Bin; Miah, M. Saef Ullah; Bhowmik, Abhijit; Sulaiman, Junaida (IEEE, 2021)
The goal of this study is to find whether exposure to Deepfake videos makes people better at detecting Deepfake videos and whether it is a better strategy against fighting Deepfake. For this study a group of people from Bangladesh has volunteered. This group were exposed to a number of Deepfake videos and asked subsequent questions to verify improvement on their level of awareness and detection in context of Deepfake videos. This study has been performed in two phases, where second phase was performed to validate any generalization. The fake videos are tailored for the specific audience and where suited, are created from scratch. Finally, the results are analyzed, and the study’s goals are inferred from the obtained data.